Responses of Vaginal Microbiota to Dietary Supplementation with Lysozyme and its Relationship with Rectal Microbiota and Sow Performance from Late Gestation to Early Lactation - Shengyu Xu; Yanpeng Dong; Jiankai Shi; Zimei Li; Lianqiang Che; Yan Lin; Jian Li; Bin Feng; Zhengfeng Fang; Zhuo Yong; Jianping Wang; De Wu (Animals, 2021)
This study was conducted to evaluate the effects of dietary lysozyme (LZM) supplementation on the vaginal microbiota, as well as the relationship between vaginal microbiota and the fecal microbiota of rectum and the reproductive performance of the sow. A total of 60 Yorkshire × Landrace sows (3–6 of parity) were arranged from day 85 of gestation to the end of lactation in a completely randomized design with three treatments (control diet, control diet + lysozyme 150 mg/kg, control diet + lysozyme 300 mg/kg). The results showed that sows fed with lysozyme increased serum interleukin-10 (IL-10, p < 0.05) on day 7 of lactation. The vaginal microbiota varied at different taxonomic levels with LZM supplementation by 16S rRNA gene sequencing. The most representative changes included a decrease in Tenericutes, Streptococcus, Bacillus and increase in Bacteroidetes, Actinobacteria, Enterococcus, and Lactobacillus (p < 0.05). There were 777 OTUs existing in both, vaginal and fecal microbiota. The addition of LZM also decreased the abundance of Tenericutes (p < 0.05) in the vagina and feces. The changes in the microbiota were correlated in some cases positively with the performance of the sow, for example, Bacillus in feces was positively correlated with the neonatal weight (p < 0.05). These results indicate that the addition of lysozyme to the diet of sow during perinatal period promote the change of vaginal bacterial community after farrowing. The variations in vaginal microbiota are also associated with the changes in the fecal microbiology of the rectum and the reproductive performance of the sow. Therefore, it is concluded that dietary supplementation with lysozyme in sows in late gestation stage until early lactation, is beneficial to establish vaginal microbiota that seems to promote maternal health and reproductive performance.